Pengaruh Sikap Auditor Terhadap Audit Investigasi Dan Whistleblowing Dalam Mendeteksi Fraud - Silvia Vasaura; Mohamad Djasuli (CV. ITTC INDONESIA, 2022)
Pengaruh Sikap Auditor Terhadap Audit Investigasi dan Whistleblowing dalam Mendeteksi Fraud. This study aims to determine: (1) The effect of the auditor's attitude on the incidence of fraud in an organisation/company. (2) The influence of the auditor's attitude towards the investigative audit on the occurrence of fraudulent financial statements. (3) The influence of the auditor's attitude towards whistle-blowing in the occurrence of fraud. The instrument used is a case of fraud. The results of this study are how to see if the auditor is ready when dealing with investigative audits and whistleblowing to detect fraud in financial statements in companies/organizations. The auditor plays an important role in this case, because whistleblowing itself can have 2 impacts, namely positive and negative. Investigative Audit itself is a process of systematically seeking, finding and gathering evidence with the aim of revealing whether an action has taken place or not and the culprit for further legal action to be taken which is supported by the attitude of the auditor in dealing with fraud cases.